The Influence of the Traditional Game Sapintrong Based on Local Wisdom on Strengthening Global Diversity Character of Third Grade Elementary School Students: Pengaruh Permainan Tradisional Sapintrong Berbasis Kearifal Lokal Terhadap Penguatan Karakter Kebhinekaan Global Kelas 3 di Sekolah Dasar - Aliyah, Izzatul; Syailin Nichla Choirin Attalina (Global Action and Education for Society, 2026)
This research aims to analyze the influence of the traditional game Sapintrong, based on local wisdom, on strengthening the character of global diversity among third-grade students at SDN 04 Panggang. The research employs a quantitative approach with a true experimental design of the randomized control group type. The research subjects consist of 63 students, comprising 32 students in the experimental class and 31 students in the control class. The research instrument is a questionnaire developed based on four elements of global diversity, including recognizing and appreciating culture, intercultural communication and interaction, reflection and responsibility toward diversity experiences, and social justice. The research results show a significant in the experimental class, with the average score rising from 50.9 to 82.3, or by 61.7%, while the control class experienced a decrease of 0.27%. the t-test indicates a significance value of 0.000 < 0.05, meaning there is a significant influence of the Sapintrong game on strengthening the character of global diversity. These findings affirm that traditional games can function not only as entertainment but also as an effective learning medium for instilling the values of the pancasila student profile, particularly the dimension of global diversity.